Evaluation of the Selection and Application of Environmentally Friendly Materials in Row Housing Design: A Case Study of Cemara Asri, Medan - Parlindungan Waruwu; Melly Andriana; Dara Wisdianti (International Journal of Mechanical, Electrical and Civil Engineering, 2026)
The use of building materials plays a crucial role in determining the quality of the built environment, particularly in the context of row housing in densely populated urban areas. This study aims to evaluate the types of materials used in the construction of row housing in Cemara Asri, Medan, with a focus on sustainability and environmental friendliness criteria. The methods employed include direct site surveys and literature studies related to the characteristics of both interior and exterior materials applied to housing units. The research findings indicate that most of the materials used—such as red bricks, ceramic tiles, clay roof tiles, and concrete ventilation blocks—possess good energy efficiency and durability potential. However, they do not fully meet sustainability standards in terms of production processes and waste management. The study also found that residents' awareness of environmentally friendly material selection remains limited, and the procurement of materials tends to follow local availability and economic considerations. These findings are expected to serve as a foundation for improving environmentally friendly material planning in row housing developments in other urban areas.